Microbiology General and applied - Nilangshu Mukhergee; Rupa Bhattacharyay; Avik Mukherjee (Ludhiana kalyani, 2008)
This book describe the studying microorganisms
Studying microorganisms Genetic,environment Microorganisms medical microbiology
Keywords: Studying microorganisms, Genetic,environment Microorganisms, medical microbiology